The benefit and risk of testosterone replacement therapy in older men: effects on lipid metabolism - Volpato, Stefano; Vigna, Giovanni B.; Fellin, Renato (Acta Biomedica Atenei Parmensis, 2010)
Over the last decades, testosterone replacement therapy for middle-aged and older men has been gaining increasing and widespread attention and popularity. Although several benefits of testosterone replacement therapy are well established, including but not limited to improvement in libido, body composition, and bone density, concerns for multiple potential adverse effects remain. In particular, concerns are frequently raised regarding the possibility that testosterone replacement therapy may increase the risks of prostate cancer and cardiovascular disease as consequence of a potential detrimental effect of testosterone on cardiovascular risk factors. This mini-review will present and discuss the current knowledge on the relationship between testosterone replacement therapy and change in lipid fractions in older men.